The four obsessions of an extraordinary executive : a leasership fable - Lencioni, Patrick (Jossey-Bass, 2000)
The publication focuses on leadership qualities and how to build a successful business organization. Written for professional and general public.
Keywords: exekutivní funkce; obchod; organizace a řízení; Organization and Administration; úspěšnost; Organizations; Executive Function; vůdcovství; psychologie, klinická psychologie; Commerce; organizace; Achievement; management, organizace a řízení zdravotnictví; Leadership